Evaluation of Microleakage under Sapphire Brackets Bonded with Three Different Orthodontic Adhesives after Thermocycling and Water Storage (An in Vitro Study) - Omaima Lateef Salman; Reem Atta Rafeeq Al-Ani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: To evaluate and compare the microleakage between enamel-adhesive, bracket-adhesiveinterfaces at occlusal and gingival sides of sapphire brackets bonded with three different light-cure adhesivesystems after thermocycling and 2 months water storage.Materials and Methods: Sapphire brackets bonded to forty eight intact extracted upper premolar randomlyassigned according to orthodontic adhesive systems used into three equal groups (n=16) with different colorcoding: Conventional Transbond XT; Transbond XT plus self-etching primer; Resin-modified glass ionomercement (RMGIC) GC Fugi Ortho LC. After bonding and thermocycling, half of samples (8 teeth) in eachgroup, tested immediately after thermocycling and 24 hours of water storage and the remaining 8 teeth wereincubated in distilled water to be tested after 2 months of water storage. After each storage interval, sampleswere subjected to a dye penetration test and examined under a stereomicroscope with image analyzersoftware to assess the degree of microleakage in mm. Data was analyzed using the non-parametric tests.Results: After both storage time intervals, RMGIC group displayed higher microleakage than other groupswith high significant differences with Transbond XT group and more microleakage seen at gingival marginthan occlusal margin in all groups. The microleakage values increased after 2 months storage, but withoutsignificant differences.Conclusion: The type of adhesive systems could effect the amount of microleakage and higher valueunder brackets bonded with RMGIC with more microleakage gingivally than occlusally. The microleakageincreased after thermocycling with 2 months water storage.